Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), dan Intellectual Capital (IC) sebagai Variabel Mediasi: Pengaruhnya pada Kinerja Keuangan Perbankan Syariah - Zaharani, Chanina Mumtaza; Aisyah, Esy Nur (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on Return on Assets (RoA) in Islamic Commercial Banks in Indonesia, with Intellectual Capital (IC) as a mediating variable during the period 2019-2023. The approach used is a quantitative method and path analysis on panel data from 9 Islamic Banks. The results show that GCG has no significant influence on RoA either directly or through IC. Conversely, CSR has a significant influence on RoA directly, but not through IC. Meanwhile, the IC variable has a significant influence on RoA. In addition, both GCG and CSR have a significant influence on IC.